Bibliometric Analysis of BiFeO3 Nanoparticle Research Development Using VOSviewer Application - Al-Ghani, Ranggaweny (Penerbit Goodwood, 2025)
Purpose: This research aimed to conduct analysis in the research of BiFeO3 nanoparticles through bibliometric analysis techniques with computational mapping used VOSviewer application. Methodology/approach: By using the publish or perish reference management tool and the Google Scholar database's collection of research article data to obtain research data article. The search was focused on the article's title and abstract with